An Unusual Case of a Coexistent Serous Cystadenoma and Intraductal Papillary Mucinous Neoplasm of Pancreas. EUS to the Rescue! - Chahal, Prabhleen; Saad, Assad J; Jeyarajah, Rohan D (JOP. Journal of the Pancreas, 2011)
Context Synchronous cystic neoplasms of pancreas are a highly rare occurrence. Case report We report a very rare case of coexistent serous cystadenoma and multi-side branch intraductal papillary mucinous neoplasm (IPMN). Conclusion To our knowledge, there has been only one previous case report in the literature of a synchronous serous cystadenoma and a solitary IPMN lesion. This case report is intended to increase the awareness of this condition while alluding to the need for diligent examination by endosonographers. It also highlights the clinical impact of endosonography on the diagnosis and management of cystic legions in the pancreas. Image: Histological slide demonstrating synchronous IPMN and serous cystadenoma.